COPD Symptoms and Risk Factors of Respiratory Disorders in Builders - Lorensia, Amelia; Suryadinata, Rivan Virlando; Savitri, Kadek Yuli Dwi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Decreased lung function is at risk for COPD (chronic obstructive pulmonary disease). Risk identification is a strategy to improve the quality of self-management, through the identification of risk factors and early symptoms of COPD. This study aims to determine the relationship between risk factors and early symptoms of COPD in builders related to pulmonary function disorders. The design of this study was case control in Rungkut District, Surabaya in September-December 2018. The research variables were lung function disorders, risk factors and early symptoms of COPD, with ordinal data scale and chi-square test analysis. This study involved 158 respondents consisting of 79 respondents with lung function disorders and 79 respondents with no lung function disorders. The highest total risk factor for COPD in both groups was smoking, and there was no significant difference (P = 0.75) on the early symptoms of COPD in the pulmonary dysfunction group and in the group with no lung function disorders. The highest total initial symptoms of COPD in both groups were chronic cough and sputum hypersecretion. However, there was no significant difference between the two groups (P = 1.00). There was no relationship between COPD risk factors and early symptoms of COPD in the pulmonary dysfunction group and the no lung function group.